Development of An Eye Tracker And Wheelchair System That Can Self Navigate In A Closed Environment - Chong, Wei Seng (2020)
A wheelchair is used to support people with mobility difficulties due to injuries or motor disabilities. For patients with serious motor disabilities who might not be able to move their hands, a joystick wheelchair that needs to be operated by hand is not feasible. Therefore, an eye tracker controlled wheelchair that only needs the user’s eye movement to control the wheelchair can be used by such patients. The aim of this project is to design and develop an eye tracker controlled wheelchair to help such patients. Two methods will be developed to control the wheelchair. The first method is to directly control the wheelchair by the instant eye movement of a user. The user can control the wheelchair to move in four directions: moving forward and backward, as well as turning left and right. The second method is developed for the user when the user needs to move from one location to another location. The user can use an eye tracker to select a location through a screen interface. The wheelchair will move to the destination with a navigation system while avoiding obstacles along the path. There are six locations provided for selection. For both methods, a node was developed for the eye tracker to retrieve the user’s eye movement. Another node was developed to collect the information from the eye tracker and uses this information to control the simulated wheelchair according to the eye movement, or to send the request to carry out the navigation. For the navigation, the mapping of the environment was completed using RVIZ to get the coordinates of the locations. The simulated wheelchair will move to the destination based on the user’s selected location while avoiding obstacles.